The doctor in front of 'Redemptor Hominis' - De Benedetto, Francesco (Medicina e Morale, 2024)
Not possessing or claiming any other references to penetrate the meaning of 'Redemptor hominis' other than those strictly inherent to his professional cultum, the doctor, who, without being a theologian or philosopher or moralist, nevertheless wishes to understand the encyclical and set it down in the reality of his life, cannot renounce designing his own key to interpretation, less pretentious or ambitious but perhaps no less valid than the others to provide an original interpretation of the profound message addressed by the Pontiff to the men of our time.